Fundamentals and applications of bionic drilling fluids - Jiang, Guancheng (Elsevier, 2021)
Theories and Technologies of Bionic Drilling Fluids covers the development and use of bionics in drilling fluids. The book considers technical challenges and upgrades to existing drilling fluid technology, presenting a case for the use of bionics in the petroleum industry alongside environmental protection. In response to the increasing need for novel technologies, the title includes insights on how nature-inspired technologies can be successfully developed to help researchers and technicians harness the power of bionics to solve practical challenges. This volume presents over a decade's worth of original research on bionic drilling fluids, offering scientists and engineers a comprehensive handbook. Drilling fluid has contributed to the safe, efficient and smooth implementation of drilling engineering for over a century. However, in recent years, oil and gas reserves have been discovered in difficult-to-access, extreme environments such as the deep ocean. Consequently, geological and ground conditions have become increasingly complex, posing a challenge to resource exploration and development. Bionics, the imitation of characteristics, structures, functions and principles from nature, offers a new approach to drilling fluid technology.